THE EFFECT OF FINANCIAL TECHNOLOGY (FINTECH) ON BANKING FINANCIAL PROFITS IN INDONESIA (CASE STUDY ON BUMN BANK KBMI 4) - Anggy Khusnul Khatima; Anas Iswanto Anwar; Muhammad Yusri Zamhuri (Jurnal Ekonomi, 2023)
This study aims to determine and analyze the effect of funding, lending and interest rates at banks on bank profitability through three indicators, namely ROA, NIM, and LDR at BUMN Banks KBMI 4, namely Bank BRI, Mandiri, and BNI after fintech. This study uses secondary data obtained from the Central Bureau of Statistics (BPS), the official website of each type of bank, and OJK. The data used is panel data consisting of 3 types of banks namely BRI, Mandiri and BNI in Indonesia in 2014-2021. The data analysis method used is Panel Data Regression using the fixed effect model. Based on the results of this study indicate that Funding has a significant negative effect on Bank Banking Profitability KBMI 4. Lending has a positive and significant effect on the Profitability of Banking KBMI 4 Banks in Indonesia. Meanwhile, interest rates have two different results which have a positive and significant effect on the profitability of Bank BUMN KBMI 4 through NIM and LDR, but have no significant effect through ROA.